Functional interplay between condensin I and topoisomerase Iiα in single-molecule DNA compaction - Yuko Tsubota; Keishi Shintomi; Kazuhisa Kinoshita; Yuki Masahara-Negishi; Yuuki Aizawa; Masami Shima; Tatsuya Hirano; Tomoko Nishiyama (Nature Communications)
Abstract Condensin I and topoisomerase IIα (topo IIα) are chromosomal ATPases essential for mitotic chromosome assembly. Mechanistically how the two ATPases cooperate to assemble mitotic chromosomes remains unknown. Here we investigate the interplay between condensin I and topo IIα at single-molecule resolution. While condensin I alone exhibits ATP-dependent DNA loop formation, it generates stable, compact structures (“lumps”) in the presence of topo IIα in a manner dependent on its C-terminal domain. These lumps predominantly contain a single condensin I complex and a single topo IIα dimer. The strand passage activity of topo IIα introduces DNA knots within the lumps, rendering them resistant to protease treatment. An ATP hydrolysis-deficient mutant of condensin I forms smaller lumps, in which the probability of DNA knotting is markedly reduced. Our findings demonstrate that topo IIα-mediated strand passage is functionally coupled with condensin I-mediated loop extrusion, providing insights into the mechanism underlying mitotic chromosome assembly.